GAMBARAN KADAR LIPID PADA PENGGUNAAN OBAT ANTI EPILEPSI TUNGGAL GENERASI PERTAMA - Dian Cahyani, Fitri Octaviana, Lyna Soertidewi, Astri Budikayanti, Joedo Prihartono (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION LONGTERM THERAPY WITH FIRST GENERATION OF ANTIEPILEPTIC DRUGS AED HAS BEEN ASSOCIATED WITH ADVERSE EFFECTS SUCH AS SERUM LIPID PROFILE CHANGES WHICH CAN INCREASE RISK OF CARDIOVASCULARAND CEREBROVASCULAR DISEASE THESE AEDS ARE COMMONLY USED IN NEUROLOGY CLINIC OF RSCM KNOWLEDGE OF LIPID PROFILE AND PREVALENCE OF DYSLIPIDEMIA ON MONOTHERAPY OF FIRST GENERATION AEDS CAN BE USED FOR PREVENTING OF CARDIOVASCULAR AND CEREBROVASCULARACCIDENTS